ChemInform Abstract: Oxidant‐Controlled Catalytic Transformations of Phenols with Unexpected Cleavage of Aromatic Rings. Issue 8 (February 2016) - Li, Wei; Song, Feijie; You, Jingsong
Abstract: A novel copper‐catalyzed oxidative coupling of electron rich phenols that involves the cleavage of a benzene ring is described to yield 3‐furanyl substituted benzofurans (III) and (V).